La science‑fiction a‑t‑elle horreur du vide ? Le cas des séries télévisées - Elaine Després; Hélène Machinal (ReS Futurae)
Gaps are central to theories of reception, because they underly any act of reading, which consists in filling them. When it comes to science fiction literature, filling these gaps gets more complicated, but what about audiovisual science fiction? Does gaps or voids – as diegetic issues, fictional themes, recurring visual signs, epistemic enigmas or structural features – play a role in the process of receiving these works? If science fiction television series rely on a system of signs that we need to reconstruct, what would be the specificities of these voids and what narrative, interpretive and aesthetic strategies should we use to fill them ? Are the possible worlds of TV science fiction built on the same grammar as those of textual science fiction? Therefore, is a grammar of TV series conceivable? Is it built on specific signs that would form a "megatext" specific to the medium, identifiable in iconographic and serial terms? To try to answer these questions, this article proposes a typology of voids in a rather large corpus of recent science fiction series. These voids can be temporal (intradiegetic or extradiegetic), spatial (archipelagic space and virtual non-places) or epistemological, and can be found as much on the level of form, story and fiction. We propose that SF TV series are hyperactive machines contrary to texts that Eco called « lazy machines ». Last but not least, the article tries to envisage how the notion of voids could be articulated to SF theory and more specifically to the famous novum proposed by Suvin.